Protective role of resveratrol against VCM-induced hepatotoxicity in male wistar rats - Alshehri, Fahad S.; Alorfi, Nasser M. (Frontiers in Pharmacology, 2023)
Background: Vancomycin is a glycopeptide antibiotic with a high risk of acute liver injury. Resveratrol is believed to protect the liver against toxicity. Aim: To investigate the ability of resveratrol to attenuate vancomycin-induced liver toxicity in rats injected with vancomycin. Method: Twenty-four adult male Wistar rats were distributed into three groups. The control group received only a vehicle, while the treated group received either vancomycin 200 (mg/kg, i.p.) only or vancomycin (200 mg/kg, i.p.) with resveratrol (20 mg/kg, oral gavage). All groups received their dose once daily for seven days. Hepatic damage was assessed by measuring biochemical parameter levels in serum, aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH). Also, antioxidants and inflammation biomarkers such as Interleukin-6 (IL-6), malondialdehyde (MDA), nitric oxide (NO), and glutathione (GSH) were measured. Furthermore, the vancomycin-induced pathological changes in the liver were evaluated by histopathological studies. Results: In the vancomycin-treated group, hepatic serum biomarkers such as AST, ALT, ALP, IL-6, and MDA were elevated, while NO and GSH were depleted. However, resveratrol co-treatment with vancomycin prevented the elevation of AST, ALT, ALP, IL-6, and MDA and it protected the liver from NO and GSH depletion. Also, regarding vancomycin-induced degeneration of hepatocytes, resveratrol co-treatment with vancomycin prevented such degeneration and improved mononuclear cells in the liver. Conclusion: The results showed that oral administration of resveratrol has a significant hepatoprotective effect against vancomycin-induced hepatotoxicity.